Thursday
March 30, 2017

Post a New Question

Posted by on .

Find the difference quotient and simplify your answer. Step by step. f(x) = 3x2 − 6x, f(x + h) − f(x) h , h ‚ 0

  • Algebra - ,

    f(x)=3x^2-6x
    f(x+h)=3(x+h)^2 -6(x+h)
    = 3x^2+6xh+3h^2-6x-6h

    so f(x+h)-f(x)= 0x^2-0x+6xh-3h^2-6h

    dividing that by h then
    6x-3h-6
    as h approaches zero, then the difference quotent= 6x-6

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question